Thermophysical Diversity of Young Lunar Crater Ejecta Revealed with LRO Diviner Observations - Cailin L. Gallinger; Jean-Pierre Williams; Catherine D. Neish; Tyler M. Powell; Catherine M. Elder; Rebecca R. Ghent; Paul O. Hayne; David A. Paige (The Planetary Science Journal)
Young (<1 Ga) craters on the Moon are known to host diverse mixtures of ejecta with varying spectral and physical properties. In this work, we examine 13 yr of bolometric surface temperature data from the Diviner Lunar Radiometer on board the Lunar Reconnaissance Orbiter over the ejecta blankets of 10 lunar craters of varying sizes ( D = 5–43 km) and ages (<10 to ∼200 Ma) to study the spatial variation in their thermophysical characteristics. We find that a one-dimensional thermal model with two free parameters—the bottom-layer bulk density, ρ _d , and the transition height between the surface and bottom-layer densities, H —is able to accurately fit these data over our study regions, in contrast to previous models that assumed a constant ρ _d . Based on the best-fit model parameters, young crater ejecta can be divided into three classes: (1) “blocky” regions with a high abundance of boulders >1 m in diameter, (2) “clastic” ejecta with varying levels of vertical density stratification, and (3) “impact melts” with high thermal inertia materials buried under a layer of less dense material. These thermophysically derived classes correlate strongly with observed morphology in high-resolution images and polarimetric signatures in decimeter-wavelength radar, and their thermophysical properties evolve distinctly with crater age. This technique represents the first time impact melt in many forms can be quantitatively distinguished by its physical properties from other types of ejecta using remote-sensing data and could have applications in validating models of impact ejecta production and deposition.